AUGGIE’S INFERIORITY COMPLEX AND ITS IMPACTS TOWARD HIS SOCIAL LIFE AS DEPICTED IN R. J. PALACIO’S NOVEL WONDER - Irfanto Suari; Hilaria Dewi Hapsari (Conscientia, 2022)
Abstract The title of this research is “Auggie’s Inferiority Complex and Its Impacts toward His Social Life as depicted in R. J. Palacio’s Novel Wonder”. This research uses psychological approach by Rohrberger & Woods and the theory of Individual Psychology by Alfred Adler. The main objective of this research is to find out the impacts of inferiority complex on the main character, Auggie. To collect the data for this research, the researchers use library research to help the researchers find the data related to the main goal of the research. All the data is taken from the novel Wonder written by R. J. Palacio. The result of this research is that Auggie’s inferiority complex gives some impacts such as he becomes an introvert, insecure, secretive, and antisocial individual. Keywords: inferiority complex, social life, impacts of inferiority complex.